A PC-based simulation platform for a quadcopter system with self-tuning fuzzy PID controllers - Abu Rmilah, M.H.Y.; Hassan, M.A.; Mardi, N.A. (John Wiley & Sons, 2016)
Nowadays, engineers rely on simulation environments to get fast, accurate results to develop complex engineering systems. This paper presents a simulation platform that is useful for students to investigate quadcopter systems. Based on real-time simulation results, the performance of the quadcopter under self-tuning fuzzy PID controllers was compared and further investigated.